Mapping the disc evolution of EX Draconis - Harlaftis, E. T.; Papadimitriou, C.; Steeghs, D.; Sokoloski, J. L.; Rutten, R. G. M.; Niarchos, P. G.; Gazeas, K.; Manimanis, V.; Boffin, H.; Zurita, C. (2002)
We observed EX Draconis in BV I colours for 40 nights, covering 3 outburst events, with the aim to study the disc evolution. Here, we present a preliminary eclipse-mapping study of some of the B band light curves obtained during the outburst in August 2000.